Podolian cattle: reproductive activity, milk and future prospects - Cosentino, Carlo; D'Adamo, Carmine; Naturali, Salvatore; Pecora, Giovanni; Paolino, Rosanna; Musto, Mauro; Adduci, Francesco; Freschi, Pierangelo (Italian Journal of Agronomy, 2018)
In the present study, an original article about Podolian cattle and its milk was performed. In detail, the following factors on reproductive career of Podolian cattle in semi-extensive and extensive rearing were analysed: age of calving, gestation lenght, calving interval length, abortions percentage, conception and calving period. Chemical and phisycal parameters (protein, fat and lactose), somatic cell count, lisozyme content and antiradical activity, with ABTS and DPPH assays, of Podolian milk in semiextensive and extensive rearing were evaluated. Finally, suggestions on future prospects of Podolian milk use were proposed: the preparation of hand soap with 5 percentage of podolian milk and the potential role of this breed for prevention and propagation of fire. The data concerning the reproductive career, milk and envinromental role of 677 cows registered in the Herdbook were analysed. The results showed that the 58.56% of the cows manifested a calving interval of 11-14 months. The reproductive activity occurred in spring; over 70% of the cows calved in the period February-April. The chemical-physical aspects of milk are in agreement with literature. It presents an high antioxidant activity values for each group (97.03% and 97.50% for ABTS and 52.09% and 52.60% for DPPH, semiextensive and extensive system respectively). The consumer test shows that the subjects appreciated the soap containing 5% of Podolian milk for different aspect. The data about environmental role were obtained from Podolian cows reared in fifteen grazing areas were monitored for five years during the summer pasture, when the Podolian cattle graze on green grazing areas located in Basilicata region (South of Italy). Therefore, an efficient management of grazing by Podolian cattle could be an important tool to prevent the fire propagation.